Anopheline antiplatelet protein from mosquito saliva regulates blood feeding behavior - Islam, Ashekul (2021)
The saliva of hematophagous arthropods is enriched with a complex mixture of antihemostatic molecules, the biological functions of which are largely unknown. Anopheline antiplatelet protein (AAPP) from malaria vector mosquito exhibits strong antiplatelet activity when bound directly to host collagen by its C-terminus and through its N-terminus with Ca 2+ -binding activity. To investigate the biological functions of AAPP in blood feeding behavior and malaria transmission, we generated transgenic Anopheles stephensi mosquito lines expressing anti-AAPP antibody single-chain fragment (scFv) in their salivary glands. The AAPP-specific collagen-binding activity was completely abolished by AAPP-scFv complex formation in the saliva. Probing and prediuresis time, feeding success, blood meal size, and fecundity, which are all fitness characteristics, were significantly reduced in the transgenic mosquitoes. However, oocysts number in these mosquitoes were not significantly reduced following blood meal intake from Plasmodium berghei-infected mice. These results show that although AAPP plays an important role in mosquito blood feeding, its neutralizing activity did not affect sporogonic development in our laboratory model, but its high fitness cost would pose a survival risk for parasite-infected mosquitoes in nature.